Relationship between maternal mindfulness and anxiety 1 month after childbirth. Issue 4 (22nd December 2016) - Yamamoto, Natsuki; Naruse, Takashi; Sakai, Mahiro; Nagata, Satoko
Abstract : Aim: To investigate the relationship between maternal mindfulness and maternal anxiety 1 month after childbirth. Methods: A cross‐sectional design was used, featuring anonymous questionnaires that were completed between July and December 2014 at two Japanese hospitals. The participants ( n = 151) completed the Mindful Attention Awareness Scale (Japanese version) and the State–Trait Anxiety Inventory Form X (Japanese version). The data analysis was carried out by using a hierarchical multiple regression. Results: The state and trait anxiety scores showed significant relationships with mindfulness, the mother's age, and the perceived difference between the expectations of motherhood before childbirth and the reality of post‐partum daily life. Furthermore, the amount of average sleep time in the past week (including naps) showed a negative association with the state anxiety score, whereas the marital relationship showed a positive association with trait anxiety. Finally, at 1 month post‐partum, the mothers with greater mindfulness scores showed lower anxiety. Conclusions: Improvements in mindfulness could help mothers to reduce their post‐partum anxiety.